Intratumoral oestrone sulphatase activity as a prognostic marker in human breast carcinoma. - Evans, T. R. (Nature Publishing Group, 1994)
Oestrone sulphatase is an important source of local synthesis of biologically active oestrogens in human breast cancer. The oestrone sulphatase enzyme in the particulate fraction of human breast carcinoma was characterised. The Km was 8.91 microM, and the Vmax was 0.022 nmol min-1 mg-1. Oestrone sulphatase activity was detected in 93 of 104 human breast carcinoma samples (89%), and mean activity was 0.041 nmol min-1 mg-1 (range 0-0.399 nmol min-1 mg-1). There was no significant correlation between intratumoral oestrone sulphatase activity and oestrogen receptor status, or with any other prognostic factors. Intratumoral enzyme levels were not associated with time to recurrence or with overall survival time. It thus appears that, although a useful source of intratumoral oestrogens, oestrone sulphatase activity is not of prognostic significance in breast carcinoma.